IS INTERNAL DEVALUATION POLICY IN THE EU EFFECTIVE? - Kersan-Škabić, Ines (Economic Annals, 2016)
This research provides indepth analysis of the causes and outcomes of internal devaluation policy in EU. It is conducted using statistical and econometric tools on a sample of three groups of EU member states: EU new member states, PIIGS, and the rest of the EU (EU-core). The analysis points to the key drivers of economic growth in the whole of the EU as being productivity and investment (and consumption in EU new member states and EU core members). Unit labour costs are relevant for GDP growth in PIIGS but with a positive sign, while for the rest of the EU it is not a significant variable. The policy of internal devaluation is unsuitable for application in any EU member states, due to individual specificities. The solution is stronger EU governance that takes the heterogeneity of EU member states into consideration in the process of creating policies and finding solutions.